Analysis Of Success Factors Of Cultural Heritage Tourism Village Pilot In Cimareme Village, Garut District - Barkah, Sarifatun Nisa; Ieke Sartika Iriany; Suseno, Novie Susanti (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The tourism village programme was established by the government directly in order to empower village communities through tourism activities. The purpose of this study is to evaluate the variables that influence the success of the formation of cultural heritage tourism villages in the village of Cimareme, Garut Regency. The problem studied is how much influence the economic, social, cultural, environmental, political, technological, infrastructure on the success of tourism. The type of research used is exploratory quantitative with a cross-sectional approach. The research sample is the Village Government, Village Community Institutions in Cimareme Village. The main focus of research is to measure and view data from independent and dependent variables at a certain point in time. The R Square value influences together or simultaneously with culture, economy, infrastructure, environment, politics, social, and technology on the success of tourism village pioneering with Adjusted R Square 0.998 or 99.90%. The implication of the research is the development of a sustainable local economy, preservation of culture and tradition, improvement of infrastructure and accessibility, empowerment of local communities.